1982
DOI: 10.1002/dev.420150111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early social experience on activity and object investigation in the ferret

Abstract: Earlier experiments have shown that many of the effects of early social isolation in the rat may be due to deprivation of social play. The isolated ferret, like the isolated rat, is hyperactive; furthermore, its hyperactivity appears to be related to deprivation of social play. However, the relationship between object investigation and social rearing is more complex in the ferret than it is in the rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…In agreement with our findings, previous studies showed reduced social activities/preference in MIA rodents ( Shi et al, 2003 ; Smith et al, 2007 ; Bitanihirwe et al, 2010 ; Malkova et al, 2012 ). Ferrets are social animals and social behaviors are important for the development and maintenance of other behaviors ( Chivers and Einon, 1982 ; Boyce et al, 2001 ). Besides affecting interactions with conspecifics, MIA also impaired interactions with humans (reduced eye contact tolerance).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our findings, previous studies showed reduced social activities/preference in MIA rodents ( Shi et al, 2003 ; Smith et al, 2007 ; Bitanihirwe et al, 2010 ; Malkova et al, 2012 ). Ferrets are social animals and social behaviors are important for the development and maintenance of other behaviors ( Chivers and Einon, 1982 ; Boyce et al, 2001 ). Besides affecting interactions with conspecifics, MIA also impaired interactions with humans (reduced eye contact tolerance).…”
Section: Discussionmentioning
confidence: 99%
“…Weiss (1975) gave a general description of play in Polecats: it involves jerky, bouncing movements, inhibited attacks and clumsy movements, and has no obvious function. Social play more closely resembles fighting than any other form of adult behaviour, but there is far more chasing and fleeing, and biting is inhibited (Poole, 1978; see also Lazar & Beckhorn, 1974;Biben, 1982;Chivers & Einon, 1982;Mankovich, 1982).…”
Section: General Behaviourmentioning
confidence: 99%
“…An absorbable paper liner may be used in the pan beneath the cage to facilitate daily disposal of urine and feces. Chivers and Einon (1982) found that some of the isolation-induced effects on behavior seen in rats also occurred in ferrets, with deprivation of rough and tumble social play causing hyperactivity that persisted into adulthood. Use of one or two additional pieces of cage board or similar substance within the cage also helps maintain cleanliness, and ferrets enjoy burrowing beneath and between the sheets of paper.…”
Section: Cagingmentioning
confidence: 99%